The Effect of Profitability, Leverage and Inflation on Stock Returns - Maulana, Yasir; Nurhumaira, Nadhifa; Hidayat, Yusuf Murtadlo (Universitas Kuningan, 2025)
This research was conducted at Building Construction Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2017-2021 period. The purpose of this study was to determine the effect of profitability, leverage and inflation on stock returns. The sample in this study were 8 Building Construction Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period, this research method uses descriptive and verification methods. Profitability, leverage and inflation variables as independent variables and stock returns as the dependent variable. Data were analyzed using Eviews 9.0. Based on the results of the F test, profitability, leverage and inflation simultaneously affect stock returns. The results of the t test show that profitability (ROA) has a positive and significant effect on stock returns, leverage (DER) has an insignificant positive effect on stock returns, inflation has a negative and insignificant effect on stock returns